WOMEN'S EMPOWERMENT AND GENDER INEQUALITY IN ADOLESCENT NUTRITIONAL STATUS: EVIDENCE FROM THE INDONESIAN FAMILY LIFE SURVEY. Issue 5 (23rd November 2017) - Kunto, Yohanes Sondang; Bras, Hilde
Summary: In contrast to the extensive knowledge on the association between women's empowerment and the nutritional status of children under the age of five, relatively little is known about the influence of women's empowerment on adolescents' nutritional status. This study aimed to assess the association between women's empowerment and gender inequalities in adolescent nutritional status. Data were from the Indonesian Family Life Survey (IFLS) covering the period 1997 to 2015, and consisted of 16, 683 observations from 13, 396 adolescents between the ages of 10 and 19 years born in 6781 families. Three indicators of women's empowerment were used: mother's education, mother's bargaining power and mother's working status. Multivariate linear regression with robust standard errors was used to examine whether and how these indicators of women's empowerment influenced adolescent nutritional status. Interaction terms were added to analyse how the association between women's empowerment and adolescent nutritional status differed by gender. The results showed that mother's education and mother's working status were significantly associated with adolescent nutritional status, particularly with height-for-age. Adolescents of well-educated mothers had a higher height-for-age while those who were raised by mothers with a blue-collar job had a lower height-for-age. Although no gender differences were found for height-for-age, gender differences for BMI-for-age were obvious, with boys having a lower BMI-for-age than girls. Interactions between indicators of mother's empowerment and gender showed that the gender gap in BMI-for-age was smaller for adolescents of more educated mothers. However, further analyses of food consumption patterns showed that boys whose mothers were more educated consumed more fast food and had higher instant noodle consumption than girls, thus suggesting gender bias in new disguise.